The Online Classroom: A Thorough Depiction of Distance Learning Spaces. Issue 1 (2nd January 2018) - McKenna, Kelly
Abstract: This study investigated the online higher education learning space of a doctoral program offered at a distance. It explored the learning space, the stakeholders, utilization, and creators of the space. Developing a successful online classroom experience that incorporates an engaging environment and dynamic community setting conducive to learning is essential in maintaining distance-student enrollment and expanding online education. Students and faculty were surveyed and responses were coded for the emergence of themes. The expanse of distance education and progression of technology has supported instructors in developing classrooms that emphasize students and incorporate both online interactive spaces and the physical space learners inhabit. Both faculty and students contribute to this classroom, and it is utilized primarily as a space where learners engage.